Resultado fiscal e desempenho econômico das prefeituras cearenses segundo indicadores selecionados - Rocha, Paloma de Sousa (2012)
It´s the aim of this work to shed light on the mayors administration in Ceara concentrating on what they do e.g for social areas and/or building environments but also it analyzes the financial autonomy of the city and the town hall accounts concerning the period from 2006 to 2010. Four signs are sketched in order to combine statics exercises trough panel data to make sure the following: tax increasing contributes to improve the financial autonomy of the cities especially afterwards but also to reduce their dependence to the Federal Union and the States; the search for the tax increasing badly affects the future investments mainly in social areas (education and health), on the other hand it becomes the futures investments more realizable.